2020
DOI: 10.5455/javar.2020.g441
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and resistance determinants in Pseudomonas aeruginosa isolated from pericarditis in diseased broiler chickens in Egypt

Abstract: Objective: This study was performed to probe the antimicrobial resistance and virulence genes profiling in Pseudomonas aeruginosa recovered from the cases of pericarditis in broiler chickens. Materials and methods: The samples ( n = 250) collected from the cases of pericarditis in broiler chickens were bacteriologically examined. Antimicrobial susceptibility was tested by disc diffusion technique. The isolates were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In agreement with our study, the positive zeta potentials were significantly associated with nano-delivery system uptake across the mucosa (58). Furthermore, garlic oil nanoemulsions of mean size 36.3 nm, of average zeta potential was -26.23 mV (with different ratio of surfactant) was reported, and polydispersity index was 0.527 showed a weak antibacterial effect on some Gramnegative bacteria (59). Our study showed that garlic oil nanoemulsion's low MIC value revealed an antibacterial effect (partial bioactivity) against ten P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our study, the positive zeta potentials were significantly associated with nano-delivery system uptake across the mucosa (58). Furthermore, garlic oil nanoemulsions of mean size 36.3 nm, of average zeta potential was -26.23 mV (with different ratio of surfactant) was reported, and polydispersity index was 0.527 showed a weak antibacterial effect on some Gramnegative bacteria (59). Our study showed that garlic oil nanoemulsion's low MIC value revealed an antibacterial effect (partial bioactivity) against ten P. aeruginosa isolates.…”
Section: Discussionsupporting
confidence: 90%
“…The extracellular pathogenic factors play a key role in P. aeruginosa infection and the most investigated are represented by exotoxin A, phospholipase C, elastase, alkaline protease, and type III secretion system [61]. Few data are available in veterinary literature about the occurrence of these factors in P. aeruginosa clinical isolates from companion [62] and farm animals [63][64][65]. In the present study, a high occurrence was found for all the pathogenic markers that we investigated, suggesting the elevated virulence potential of the isolates, as well as reported in human clinical isolates [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…(Tawakol et al, 2018) reported that P. aeruginosa isolates were highly sensitive to colistin sulphate and amikacin (90%) for each, and (Hassan et al, 2020) recorded that the most effective antibiotics were imipenem and colistin (100% for each), and amikacin (92%). Colistin is considered a significant option for treatment of MDR-resistant P. aeruginosa infections due to its bactericidal effect (Gill et al,…”
Section: Samplesmentioning
confidence: 99%